THE ACTUALIZATION OF THE IMPLEMENTATION OF ENVIRONMENTAL AND SUSTAINABLE PRINCIPLES ON INVESTMENT IN THE TOURISM SECTOR - Lis Julianti (NOTARIIL Jurnal Kenotariatan, 2024)
The purpose of this study is to examine and analyze the application of the principles of sustainability and environmental awareness in investment activities in the tourism sector. Investment in the tourism industry brings chaos to values and norms that have an impact on the environmental order and community life in various regions in Indonesia. Often physical development is carried out in areas that endanger the sustainability of the natural environment or by the community. The results of the study indicated that the Principle of Sustainability and Environmental Insight in the legal policy of investment in the tourism sector is a planned principle to integrate economic, environmental, and socio-cultural dimensions to be able to improve the welfare of the community now and in the future. The principle of sustainability and environmental insight is one of the efforts to save natural resources and synchronize aspects of conservation with aspects of wise utilization so that development in the tourism sector does not result in long-term losses.